Military Deployment and its Consequences for Families - MacDermid Wadsworth, Shelley; Riggs, David S.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
We are only beginning to comprehend the extent of the challenges faced by men and women serving in the military--a vast web of difficulties that include those left behind for families when service members leave for combat, and the ones that loom over families when they return. The contributors to Military Deployment and its Consequences for Families understand in depth the complexities of military life, and how individual sacrifices translate into stressors for partners and children. Focusing on key areas such as relationship and parenting issues and the effects of wounds and injuries, chapters span the diversity of active duty, veteran, National Guard, and Reserve families, including LGB families and divorced and single service members. These findings on challenges, resources, and coping strategies give readers expert guidance in providing services for military families and helping shape the agenda for further research. Among the topics covered: Relational tension in couples during reintegration following deployment. Parenting practices and emotion regulation in National Guard and Reserve families. Tension between family and career: competency-based perceptions of women and mothers. Towards an improved understanding of post-deployment reintegration. Combat-related post-traumatic stress disorder and families. Community support and unmet needs among families of persons with TBI. Military Deployment and its Consequences for Families focuses on military mental health and well-being, and deserves the attention of researchers and practitioners working in this important field.
Research and Training about Military Families: Where Are We?- Evolution of a Research Agenda -- I. Relational Functioning -- Bridging the Distance: Illustrations of Real-Time Communication of Support between Partners and Deployed Members of the National Guard -- Relational Turbulence within Military Couples During Reintegration Following Deployment -- Feasibility of Telephone Support Groups for Spouses of Returning Iraq and Afghanistan Service Members -- II. Parenting and Child Outcomes -- General and Specialist Health Care Utilization in Military Children of Army Service Members Who Are Deployed -- Parenting Practices and Emotion Regulation in National Guard and Reserve Families: Early Findings from the After Deployment Adaptive Parenting Tools/ADAPT study -- Lesbian, Gay, and Bisexual Military Families: Visible But Legally Marginalized -- III. Single Service Members -- Pre-deployment Well-being among Single and Partnered National Guard Soldiers: The Role of their Parents, Social Support, and Stressors -- Towards a Better Understanding of Post-Deployment Reintegration -- Young Veterans and the Transition to Civilian Employment: Does Marital Status Matter?- Recent Developments in the Uneasy Tension Between Family and Career: Competency-Related Perceptions of Women and Mothers -- IV. Family Sequelae of Wounds and Injuries -- The Effects of Wounds of War on Family Functioning in a National Guard Sample: An Exploratory Study -- Resources and Coping Strategies Among Caregivers of Operation Iraqi Freedom (OIF) and Operation Enduring Freedom (OEF) Veterans with Polytrauma and Traumatic Brain Injury -- Combat-related Posttraumatic Stress Disorder and Families -- Community-Based Support and Unmet Needs Among Families of Persons with Brain Injuries: A Mixed Methods Study with the Brain Injury Association of America State Affiliates.
Keywords: Social sciences; Social policy; Psychic research; Social Sciences; Family; Psychology Research; Social Policy